Generation of a More Immunogenic Measles Vaccine by Increasing Its Hemagglutinin Expression - Julik, Emily (J Virol, 2016)
Imported measles virus (MV) outbreaks are maintained by poor vaccine responders and unvaccinated people. A convenient but more immunogenic vaccination strategy would enhance vaccine performance, contributing to measles eradication efforts. We report here the generation of alternative pediatric vaccines against MV with increased expression of the H protein in the background of the current MV vaccine strain. We generated two recombinants: MVvac2-H2, with increased full-length H expression resulting in a 3-fold increase in H incorporation into virions, and MVvac2-Hsol, vectoring a truncated, soluble form of the H protein that is secreted into the supernatants of infected cells. Replication fitness was conserved despite the duplication of the H cistron for both vectors. The modification to the envelope of MVvac2-H2 conferred upon this virus a measurable level of resistance to in vitro neutralization by MV polyclonal immune sera without altering its thermostability. Most interestingly, both recombinant MVs with enhanced H expression were significantly more immunogenic than their parental strain in outbred mice, while MVvac2-H2 additionally proved more immunogenic after a single, human-range dose in genetically modified MV-susceptible mice. IMPORTANCE Measles incidence was reduced drastically following the introduction of attenuated vaccines, but progress toward the eradication of this virus has stalled, and MV still threatens unvaccinated populations. Due to the contributions of primary vaccine failures and too-young-to-be-vaccinated infants to this problem, more immunogenic measles vaccines are highly desirable. We generated two experimental MV vaccines based on a current vaccine's genome but with enriched production of the H protein, the main MV antigen in provoking immunity. One vaccine incorporated H at higher rates in the viral envelope, and the other secreted a soluble H protein from infected cells. The increased expression of H by these vectors improved neutralizing responses induced in two small-animal models of MV immunogenicity. The enhanced immunogenicity of these vectors, mainly from the MV that incorporates additional H, suggests their value as potential alternative pediatric MV vaccines.